Targeted Drug Delivery Systems: Current Trends and Future Prospects - Gehlot, Praveen Singh; Patel Maheka Lalitbhai (AG Volumes, 2025)
The majority of dosage forms available today have subpar biopharmaceutical and pharmacokinetic qualities. In order to prevent harm to other tissues or organs, a suitable "drug delivery system" that delivers the active drug molecule only to the site of action has to be created. A technique for giving medications to patients at the intended location or site of action is called targeted drug delivery. Targeted drug delivery is one of the most innovative approaches to sickness diagnosis and treatment in the medical sciences. Review the many studies on current developments and potential future directions in targeted drugs delivery systems in this article. The review found that TDD improves treatment effectiveness by reducing side effects and dose requires. To improve medication transport and release, a variety of carriers have been investigated, including as nanoparticles, liposomes, micelles, and biodegradable polymers. Effectively targeting many tumour locations is still a difficulty in cancer therapy, despite attempts to create highly selective delivery methods. It is expected that as TDD systems develop, they will play a bigger part in treating complicated illnesses including cancer, neurological problems, and autoimmune issues, opening up new possibilities in precision medicine.